The Effect of Service Quality Dimensions of District Office Employees on Community Satisfaction - Anisa Nova Ramadhani; Nur Achmad (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this research is to analyze the influence of service quality dimensions of sub-district office employees on community satisfaction in Sendangijo village, Selogiri District. The type of research used in the research uses quantitative methods. The population in this study were people aged 17-40 years in Sendangijo Village, Selogiri District, totaling 715 people. The sampling technique in this research is non-probability sampling. The number of samples in this study was 107 respondents. The data source for this research is primary data. The data analysis technique in this research uses the Classic Assumption Test, multiple linear regression test, and hypothesis test. The results of the research show that the reliability of sub-district office employees has a positive and significant effect on community satisfaction. The responsiveness of sub-district office employees has a positive and significant effect on community satisfaction. Assurance/guarantees held by subdistrict office employees have a positive and significant effect on community satisfaction. The empathy possessed by subdistrict office employees has a positive and significant effect on community satisfaction. Tangible/physical evidence owned by subdistrict office employees has a positive and significant effect on community satisfaction.